Targeting quorum sensing for manipulation of commensal microbiota - Zachary Ziegert; Matthew Dietz; Max Hill; Marjais McBride; Elizabeth Painter; Mikael H. Elias; Christopher Staley (BMC Biotechnology)
Abstract Bacteria communicate through the accumulation of autoinducer (AI) molecules that regulate gene expression at critical densities in a process called quorum sensing (QS). Extensive work using simple systems and single strains of bacteria have revealed a role for QS in the regulation of virulence factors and biofilm formation; however, less is known about QS dynamics among communities, especially in vivo. In this review, we summarize the diversity of QS signals as well as their ability to influence “non-target” behaviors among species that have receptors but not synthases for those signals. We highlight host-microbe interactions facilitated by QS and describe cross-talk between QS and the mammalian endocrine and immune systems, as well as host surveillance of QS. Further, we describe emerging evidence for the role of QS in non-infectious, chronic, microbially associated diseases including inflammatory bowel diseases and cancers. Finally, we describe potential therapeutic approaches that involve leveraging QS signals as well as quorum quenching approaches to block signaling in vivo to mitigate deleterious consequences to the host. Ultimately, QS offers a previously underexplored target that may be leveraged for precision modification of the microbiota without deleterious bactericidal consequences.